Identifying Multiomic Signatures of X‐Linked Retinoschisis‐Derived Retinal Organoids and Mice Harboring Patient‐Specific Mutation Using Spatiotemporal Single‐Cell Transcriptomics - Yueh Chien; You‐Ren Wu; Chih‐Ying Chen; Yi‐Ping Yang; Lo‐Jei Ching; Bo‐Xuan Wang; Wei‐Chao Chang; I‐Hsun Chiang; Pong Su; Shih‐Yu Chen; Wen‐Chang Lin; I‐Chieh Wang; et al. (Advanced Science)
Abstract X‐linked retinoschisis (XLRS) is an inherited retinal disorder with severe retinoschisis and visual impairments. Multiomics approaches integrate single‐cell RNA‐sequencing (scRNA‐seq) and spatiotemporal transcriptomics (ST) offering potential for dissecting transcriptional networks and revealing cell‐cell interactions involved in biomolecular pathomechanisms. Herein, a multimodal approach is demonstrated combining high‐throughput scRNA‐seq and ST to elucidate XLRS‐specific transcriptomic signatures in two XLRS‐like models with retinal splitting phenotypes, including genetically engineered (Rs1emR209C) mice and patient‐derived retinal organoids harboring the same patient‐specific p.R209C mutation. Through multiomics transcriptomic analysis, the endoplasmic reticulum (ER) stress/eukryotic initiation factor 2 (eIF2) signaling, mTOR pathway, and the regulation of eIF4 and p70S6K pathways are identified as chronically enriched and highly conserved disease pathways between two XLRS‐like models. Western blots and proteomics analysis validate the occurrence of unfolded protein responses, chronic eIF2α signaling activation, and chronic ER stress‐induced apoptosis. Furthermore, therapeutic targeting of the chronic ER stress/eIF2α pathway activation synergistically enhances the efficacy of AAV‐mediated RS1 gene delivery, ultimately improving bipolar cell integrity, postsynaptic transmission, disorganized retinal architecture, and electrophysiological responses. Collectively, the complex transcriptomic signatures obtained from Rs1emR209C mice and patient‐derived retinal organoids using the multiomics approach provide opportunities to unravel potential therapeutic targets for incurable retinal diseases, such as XLRS.